The influence of model resolution on the simulated sensitivity of North Atlantic tropical cyclone maximum intensity to sea surface temperature. (10th July 2016) - Strazzo, S. E.; Elsner, J. B.; LaRow, T. E.; Murakami, H.; Wehner, M.; Zhao, M.
Abstract: Global climate models (GCMs) are routinely relied upon to study the possible impacts of climate change on a wide range of meteorological phenomena, including tropical cyclones (TCs). Previous studies addressed whether GCMs are capable of reproducing observed TC frequency and intensity distributions. This research builds upon earlier studies by examining how well GCMs capture the physically relevant relationship between TC intensity and SST. Specifically, the influence of model resolution on the ability of a GCM to reproduce the sensitivity of simulated TC intensity to SST is examined for the MRI‐AGCM (20 km), the GFDL‐HiRAM (50 km), the FSU‐COAPS (0.94°) model, and two versions of the CAM5 (1° and 0.25°). Results indicate that while a 1°C increase in SST corresponds to a 5.5–7.0 m s −1 increase in observed maximum intensity, the same 1°C increase in SST is not associated with a statistically significant increase in simulated TC maximum intensity for any of the models examined. However, it also is shown that the GCMs all capably reproduce the observed sensitivity of potential intensity to SST. The models generate the thermodynamic environment suitable for the development of strong TCs over the correct portions of the North Atlantic basin, but strong simulated TCs do not develop over these areas, even for models that permit Category 5 TCs. This result supports the notion that direct simulation of TC eyewall convection is necessary to accurately represent TC intensity and intensification processes in climate models, although additional explanations are also explored. Key Points: The climate models examined do not reproduce the observed sensitivity of TC intensity to SST The climate models realistically simulate the thermodynamic conditions needed for intense TCs The most intense simulated TCs do not occur over areas with optimal thermodynamic conditions